Structural insights into human signal peptide peptidase - Gaoxingyu Huang; Xuefei Guo; Jiaoni Wang; Xiaofei Ge; Fang Kong; Zilin Shen; Xu Wang; Chuangye Yan; Jianlin Lei; Yigong Shi; Rui Zhou (Proceedings of the National Academy of Sciences, 2025)
The signal peptide peptidase (SPP) remains the only intramembrane protease family that is yet to be structurally characterized. Here, we report the cryoelectron microscopy (cryo-EM) structures of human SPPL2a in two functional states: ligand-free and inhibitor-bound, at average resolutions of 3.3 and 3.6 Å, respectively. SPPL2a contains nine transmembrane helices with a conserved fold for the SPP and presenilin families. In the ligand-free state, an antiparallel β-hairpin is already formed near the active site, reminiscent of presenilin 1 (PS1) in its substrate-bound state. Binding by the small molecule inhibitor L685,458 triggers further conformational rearrangement in SPPL2a. Together with the cryo-EM structure of compound E-bound PS1, our findings reveal insights into selective inhibitor recognition and substrate gating by aspartyl intramembrane proteases. Structure-based sequence analysis unveils key differences between the SPP and presenilin families that underlie their function and assembly.